2014
DOI: 10.1186/1478-811x-12-19
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 alters Wnt-dependent migration and proliferation in neuroectodermal stem cells: implications for autism spectrum disorders

Abstract: Prostaglandin E2 (PGE2) is a natural lipid-derived molecule that is involved in important physiological functions. Abnormal PGE2 signalling has been associated with pathologies of the nervous system. Previous studies provide evidence for the interaction of PGE2 and canonical Wnt signalling pathways in non-neuronal cells. Since the Wnt pathway is crucial in the development and organization of the brain, the main goal of this study is to determine whether collaboration between these pathways exists in neuronal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(83 citation statements)
references
References 130 publications
(138 reference statements)
4
75
0
Order By: Relevance
“…Wong et al reported that in neuronal cells, through PKA and PI‐3 K, prostaglandin E2 can activate the canonical Wnt signaling pathway and alter the average speed of migration in Wnt‐activated cells. Thus, Ptgds may also exert its effect on neuronal migration through the Wnt signaling pathway (Wong et al, 2014). Although this is an animal study and focuses solely on one aspect of brain development, our findings suggest a novel non‐enzymatic function of Ptgds protein in brain neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al reported that in neuronal cells, through PKA and PI‐3 K, prostaglandin E2 can activate the canonical Wnt signaling pathway and alter the average speed of migration in Wnt‐activated cells. Thus, Ptgds may also exert its effect on neuronal migration through the Wnt signaling pathway (Wong et al, 2014). Although this is an animal study and focuses solely on one aspect of brain development, our findings suggest a novel non‐enzymatic function of Ptgds protein in brain neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 is important in various brain functions, including the masculinization of the brain and behavior (Amateau & McCarthy, ; Lenz et al ., ), dendritic spine formation (Amateau & McCarthy, ), synaptic plasticity (Koch et al ., ), calcium regulation in growth cones (Tamiji & Crawford ), and the survival, proliferation, migration and differentiation of neural stem cells (Jiang et al ., ). Moreover, it is capable of modifying the signaling of crucial developmental pathways, including the Wnt signaling pathway (Buchanan & DuBois, ; Evans, ; Goessling et al ., ; Wong et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In vitro cell migration assays using mouse NSCs indicate that Wnt/β-catenin signaling also promotes cell migration via cross talk with prostaglandin E2 (PGE2) signaling. This pathway leads to transcriptional upregulation of Ctnnb1 , Ptgs2 , Ccnd1 , Mmp9 [137] - all of which, likely not coincidentally, have been linked to the etiopathology of ASD and Scz [138,139,140,141,142,143,144,145]. …”
Section: Neural Precursor Migrationmentioning
confidence: 99%